Enhanced Biofilm Formation by Ferrous and Ferric Iron Through Oxidative Stress in Campylobacter jejuni - Oh, Euna; Andrews, Katelyn J.; Jeon, Byeonghwa (Frontiers in Microbiology, 2018)
Campylobacter is a leading foodborne pathogen worldwide. Biofilm formation is an important survival mechanism that sustains the viability of Campylobacter under harsh stress conditions. Iron affects biofilm formation in some other bacteria; however, the effect of iron on biofilm formation has not been investigated in Campylobacter. In this study, we discovered that ferrous (Fe2+) and ferric (Fe3+) iron stimulated biofilm formation in Campylobacter jejuni. The sequestration of iron with an iron chelator prevented the iron-mediated biofilm stimulation. The level of total reactive oxygen species (ROS) in biofilms was increased by iron. However, the supplementation with an antioxidant prevented the total ROS level from being increased in biofilms by iron and also inhibited iron-mediated biofilm stimulation in C. jejuni. This suggests that iron promotes biofilm formation through oxidative stress. Based on the results of fluorescence microscopic analysis, Fe2+ and Fe3+ enhanced both microcolony formation and biofilm maturation. The levels of extracellular DNA and polysaccharides in biofilms were increased by iron supplementation. The effect of iron on biofilm formation was also investigated with 70 C. jejuni isolates from raw chicken. Regardless of the inherent levels of biofilm formation, iron stimulated biofilm formation in all tested strains; however, there were strain variations in iron concentrations affecting biofilm formation. The biofilm formation of 92.9% (65 of 70) strains was enhanced by either 40 µM Fe2+ or 20 µM Fe3+ or both (the iron concentrations that enhanced biofilm formation in C. jejuni NCTC 11168), whereas different iron concentrations were required to promote biofilms in the rest of the strains. The findings in this study showed that Fe2+ and Fe3+ contributed to the stimulation of biofilm formation in C. jejuni through oxidative stress.